The Influence of Internal Communication and Compensation on Employee Performance through Organizational Commitment - M. Zahari; Ali Akbar; Notman Boce (Dinasti Publisher, 2024)
This study seeks to describe internal communication, remuneration, organizational commitment, and employee performance. It investigates the impact of internal communication and compensation on employee performance using organizational commitment. Employees from Jambi Province's Financial Management and Regional Revenue Agency serve as the research subjects. The research uses descriptive and verificative methods with PLS analysis. The descriptive analysis results show that internal communication is categorized as good. Compensation, organizational commitment, and performance are categorized as high. Based on the PLS analysis, the research findings are: 1) Internal communication and compensation have a positive and significant effect on organizational commitment. 2) Internal communication and compensation have a positive and significant effect on employee performance. 3) Organizational commitment has a positive and significant effect on employee performance. 4) Internal communication and compensation have a positive and significant effect on employee performance, mediated by organizational commitment, at the Financial Management and Regional Revenue Agency of Jambi Province.